Spinal Nerve Root Enhancement on MRI Scans in Children: A Review. Issue 2 (14th September 2015) - Kontzialis, Marinos; Poretti, Andrea; Michell, Hans; Bosemani, Thangamadhan; Tekes, Aylin; Huisman, Thierry A.G.M.
ABSTRACT: Spinal nerve root enhancement in pediatric patients is generally nonspecific, and clinical and laboratory correlation is essential. Nerve root enhancement indicates lack of integrity of the blood‐nerve barrier. In this review, we will present a range of pediatric conditions that can present with spinal nerve root enhancement including inflammatory, infectious, hereditary, and neoplastic causes. Familiarity with the various pathologic entities associated with spinal nerve root enhancement is important for a concise differential diagnosis in the appropriate clinical setting. This will avoid unnecessary additional investigations.